Case series of late complications after transcatheter mitral annuloplasty using Cardioband and surgical treatment options. Issue 6 (4th March 2021) - Awad, George; Varghese, Sam; Wacker, Max; Mkrtchyan, Tigran; Slottosch, Ingo; Fadel, Mohammad; Wippermann, Jens; Scherner, Maximilian
Abstract: Background: Treatment of functional mitral regurgitation using transcatheter techniques such as the Cardioband annuloplasty device (Edwards Lifesciences) has gained wide acceptance in the recent years. However, complications of such devices are rarely reported. Methods: Here, we present a case series involving two patients with dislocation of the Cardioband device and discuss the surgical management. Results: In the former the valve was re‐repaired by surgical implantation of an annuloplasty ring, and in the latter the valve had to be replaced due to severe damage of the mitral valve annulus. Both patients had an uncomplicated course and were discharged to rehabilitation Center. Conclusion: Dislocation of the Cardioband devices can be successfully managed by surgical approaches. Depending on the extent of damage to the mitral valve annulus, the valve could be re‐repaired or should be repalced.